Eğitim Fakültesi Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi Anabilim Dalı öğrencilerinin bireysel çalgı eğitimi dersine yönelik tutumlarının incelenmesi - Konakcı, Nihan (My University, 2010)
EĞİTİM FAKÜLTESİ GÜZEL SANATLAR EĞİTİMİ BÖLÜMÜ MÜZİK EĞİTİMİ RENCİLERİNİN BİREYSEL ÇALGI EĞİTİMİ DERSİNE YÖNELİK TUTUMLARININ İNCELENMESİ Bu tez çalışmasında, Eğitim Fakülteleri Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi nda yürütülmekte olan bireysel çalgı eğitimi derslerine yönelik öğrenci tutumları araştırılmıştır. Bu doğrultuda, öğrencilerin bireysel çalgı eğitimi dersine yönelik tutumlarının çeşitli demografik özelliklerine, ders ile ilgili görüşlerine ve başka değişkenlere göre farklılaşma durumları incelenmiştir. Tarama modeline uygun olarak düzenlenen araştırmanın evrenini Eğitim Fakülteleri Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi rencileri, örneklemini ise İstanbul, Bolu ve İzmir il sınırları içerisinde bulunan; Marmara Üniversitesi, Abant İzzet Baysal Üniversitesi ve Dokuz Eylül Üniversiteleri’nin Eğitim Fakülteleri Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi Anabilim Dalları lisans I, II, III ve IV. sınıf öğrencileri oluşturmaktadır. Araştırmada, 358 öğrenciden oluşan örneklem grubunun, bireysel çalgı eğitimi dersine yönelik tutumlarının belirlenmesi amacıyla, Bireysel Çalgı Eğitimi Dersine Yönelik Tutum Ölçeği ile öğrencilerin demografik özelliklerini belirleyen Kişisel Bilgi Formu kullanılmıştır. Araştırma kapsamında gerçekleştirilen literatür çalışmasında, konu ile ilgili yerli ve yabancı kaynaklar taranarak, bu konuda yapılan araştırmalar incelenmiştir. Ölçek ve Kişisel Bilgi Formu yoluyla elde edilen veriler analiz edilmiş, tablolar halinde düzenlenerek yorumlanmıştır. Yapılan analizler sonucunda Eğitim Fakültesi Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi rencilerinin bireysel çalgı eğitimi dersine yönelik tutumlarının olumlu olduğu sonucuna varılmıştır. Bununla beraber, öğrencilerin bu derse yönelik tutumlarında etkili olan çeşitli değişkenler ve tutumun alt boyutlarına göre farklılaşma söz konusu olduğu belirlenmiştir. Araştırmanın son bölümünde, araştırma sonuçları çerçevesinde konu ile ilgili görüşler ve yapılacak yeni çalışmalar için öneriler sunulmaktadır. algı eğitimi, çalgı eğitimi dersi tutumu.

EXAMINATION OF THE ATTITUDES OF THE STUDENTS OF THE DEPARTMENT OF MUSIC EDUCATION OF FINE ARTS TOWARDS THE LESSONS OF INDIVIDUAL INSTRUMENT TRAINING In this thesis study, the attitudes of the students of the department of the music education of fine arts towards the lessons of Individual Instrument Training have been reviewed. In this respect, the various demographic specifications of the students towards individual instrument trainings and their points of view regarding the lessons as well as their differential status according to the some variables have been reviewed and examined accordingly. The universe of the search organized in conformity with the scanning model constitutes the students of the department of the music education of fine arts towards the lessons of individual instrument training and on the other hand, the sample of the search constitutes I, II, III and IV graders of the students of Department of Music Education of Fine Arts towards the lessons of Individual Instrument Training from Marmara University, Abant İzzet Baysal University and Dokuz Eylül University located in Istanbul, Bolu and Izmir provincial borders. In this research, in order to learn about the attitudes of the students towards individual instrument training of the sample group consisted of 358 students, the Individual Information Form that assigns the attitude scale and demographic status of the students regarding the Individual Instrument Training has been used. In the litterateur review that has been performed within the scope of the research, the research activities in this subject have been examined by scanning the domestic and foreign sources. The data provided by means of scale and Individual Information Form has been analyzed and commented by organizing them in the form of schedule. As a result of the analysis, it is understood that the attitudes of the students of the department of the music education of fine arts towards the lessons of Individual Instrument Training are affirmative. In addition, it is ascertained that the differentiation is discussed according to the various variables that are determinant and effective in the attitudes of the students toward the said lesson and lower dimension of the attitudes. At the final chapter of the research, within the framework of the research results, the views and proposals for the further activities have been submitted accordingly. Key words: Music education, instrument education, instrument education lesson attitude.
Keywords: Müzik_Eğitim